A Combined XPS and Computational Study of the Chemical Reduction of BMP‐TFSI by Lithium. Issue 12 (6th October 2022) - Forster‐Tonigold, K.; Buchner, F.; Bansmann, J.; Behm, R. J.; Groß, A.
Abstract: Employing density functional theory (DFT) calculations and X‐ray photoelectron spectroscopy (XPS), we identify products of the reaction of the ionic liquid N, N ‐butylmethylpyrrolidinum bis(trifluoromethylsulfonyl)imide (BMP‐TFSI) with lithium in order to model the initial chemical processes contributing to the formation of the solid electrolyte interphase in batteries. Besides lithium oxide, sulfide, carbide and fluoride, we find lithium cyanide or cyanamide as possible, thermodynamically stable product in the Li‐poor regime, whilst Li3 N is the stable product in the Li‐rich regime. The thermodynamically controlled reaction products as well as larger fragments of TFSI persisting due to kinetic barriers could be identified by a comparison of experimentally and computationally determined core level binding energies. Abstract : Model studies can reveal the initial chemical processes contributing to the formation of the solid electrolyte interphase in batteries. We employed XPS experiments and DFT calculations to study the reaction of the ionic liquid BMP‐TFSI with Li. The thermodynamically controlled reaction products as well as larger fragments of TFSI persisting due to kinetic barriers could be identified.